Valuasi Ekonomi Ekosistem Mangrove Berbasis Ekowisata pada Objek Wisata Edupark Kota Semarang - Putri, Dian Khoiriyani; Pujiati, Amin; Melati, Inaya Sari (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to assess the economic value of the Mangrove Edupark ecotourism area in Semarang City through an economic valuation approach. This study uses the travel cost method and the contingent valuation approach to measure the amount of willingness to pay (WTP) of visitors for the sustainability of the mangrove ecosystem. A survey was conducted on 35 respondents who had met certain criteria, and the results of the regression analysis showed that the number of visits, travel costs, income, and distance from home had a significant effect on WTP. On the other hand, the age variable did not have a significant impact. The results showed that the average WTP of respondents reached IDR 4,742.86 per individual, with a total value of IDR 166,000. This finding shows that there is public concern for environmental sustainability as well as support for the development of conservation-based tourism. Therefore, the results of this study can be used as a basis for formulating strategic policies for the management of sustainable mangrove ecotourism areas, as well as increasing community involvement in coastal conservation efforts.